Letter (copy) : Basque Children's Concert
038-0143-001 Organisation FEA/1670 14th April, 1938. Miss B.L. Arne, Basque Children's Committee, 53, Marsham Street, S.W.1 Dear Miss Arne, BASQUE CHILDREN'S CONCERT. As promised, I now send you a batch of envelopes addressed to Women's Sections, etc., of the Labour Party to whom you could send a circular regarding the Basque Children's Concert. Yours sincerely, Secretary, Organisation Department. Envelopes. 292/946/38/143